Stages of lecturers' concern in utilizing Learning Management System (LMS) in a higher education institution / Ina Suraya Masrom - Masrom, Ina Suraya (2013)
The rapid development of Information and Communication Technology (ICT) has driven all Higher Education Institutions (HEI) to compete in utilizing e-learning among lecturers and students. Therefore, the HEIs in Malaysia started integrating Learning Management System(LMS) tools into their teaching and learning activities accordance with the increasing availability of LMS on campuses. The purpose of this study is to explore the stages of lecturers' concerns in utilizing LMS in a higher educational setting. A total of 143 lecturers were randomly stratified from Universiti Teknologi MARA(UiTM), Shah Alam in the three faculties (strata).This study adopted and adapted the Stages of Concern Questionnaire(SOCQ) in Concern Based Adoption Model (CBAM) as its theoretical framework. A descriptive and rigorous analysis survey design was used to address the research questions. Profiles of lecturers' concerns were generated and overall, the findings found that lecturers' high concerns were awareness, self and task concerns, with tailing-up of impact- refocusing concerns. T-test and ANOVA analysis were used to analyze if there is any significant difference between stage of concern in LMS adoption and demographic variables such as gender, age and teaching years. This study found that there was a significant difference between age and stage of concern. However, there was no significant difference between stage of concern and gender and teaching years.Consequently, strategies to best facilitate the utilization of LMS to the maximum were suggested in this study and implied a good management practice. Finally, recommendations for future study were also discussed in this study.